Consumption Response to Credit Expansions: Evidence from Experimental Assignment of 45,307 Credit Lines - Aydin, Deniz (American Economic Review, 2022)
In a field experiment that constructs a randomized credit limit shock, participants borrow to spend 11 cents on the dollar in the first quarter and 28 cents by the third year. Effects extend to those far from the limit, those who had the new limits as available credit, and those with a liquid asset buffer. In the short-run, flexible and installment contracts are used in tandem, with unconstrained using installments more. Long-run borrowing is predominantly using installments. Near limits, participants borrow when credit expands but save out of constraints when limits are tight. Findings support a buffer-stock interpretation emphasizing precautionary saving. (JEL C93, E21, G21, G51, O12, O16)